DEVELOPMENT AND INFLUENCE OF SPEED POWER ON RESULTS PROGRESSION OF LOW VISION JAVELIN THROWERS - Milan Matić; Srđan Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Power is a motor skill important for low vision javelin throwers. The motor skill development (power, speed, endurance etc.) linked to the fact that javelin is the lightest throwing device, we come to conclusion that the result in this discipline depends much more on the speed and flexibility than on the power. Nevertheless, development of speed power significantly influences the acquiring of good results in above mentioned discipline. While working with low vision sportsmen the attention should be focused on possible limitations in training of power that could be determined by some kind of illness or injury primarly caused the low vision. Experimental method od survey based on one sample was applied (case study). Equipment used in the experiments were adjusted to the needs, age and level of condition of examinee- Grlica Miloš (current European Record Breaker, 3rd on the World's Championship 2012 in New Zealand, discipline of javlin throwing, category F12). The survey consisted of two-months cycle in the period from 01/04/2012 until 01/06/2012 as a part of preparation for Paralympic Games in London 2012. Measured variables include: 5kg ball throwing in front and above, standing long jump, 4kg ball throwing exercise aut. Based on the applied tests a conclusion can be made that the impact of force on acquiring better results, in this discipline, is very strong. Regardless the acquired results, in our opinion too big and too fast improvement in this area of physical preparation can be contraproductive due to the occurence of inadequate movements in joints which are esential for the discipline. Power development is definitely crucial segment in modeling of training process for javelin throwers. There are many surveys and articles about this topic but very little focusing on disabled people. Future work should examine special characteristics and differences regarding this population.